Co-development strategy of gas and electricity in developing countries. Issue 5 (3rd September 2019) - Kim, Jong-Hyun; Lee, Yong-Gil
ABSTRACT: There have been significant changes in global energy initiatives following the shale gas developments, predominantly in North America. Due to the over-supply of shale gas, local gas prices are steadily declining in North America. In the case of continuous decreasing prices of gas, it is expected that the increase in the economic efficiency of gas power generation will lead global oil companies to enter the gas power generation sector in developing and under-developed countries possessing gas reserves. Global oil companies co-develop natural gas and electricity concurrently in developing/under-developed countries. Global oil companies now feature electricity generation as a key business area. Global electric utilities respond to global oil companies' entry into electricity production by cross-enter into gas development. This paper examines recent industrial dynamics that could considerably influence future natural gas and power generation markets due to the co-development strategy of global oil companies and electric utilities. This paper shows the boundary of energy business concerning electricity and gas is blurring.